2022
DOI: 10.1108/whatt-10-2021-0139
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability as a success factor for tourism destinations: a systematic literature review

Abstract: PurposeThis study sought to assess the extent to which tourism research has considered sustainability as a success factor for tourism destinations. It also aims to identify the relevance of the economic, environmental and socio-cultural dimensions of sustainability for tourist destination success, identify gaps in the literature and draw theoretical and practical implications and make recommendations.Design/methodology/approachThe research methodology consists of a systematic literature review on sustainabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…In past research studies, scholars have identified various leadership styles which are practiced in organizations based on the extent of need. However, in today’s fast-growing and competitive world, the sustainability in the tourism industry has knowingly enriched drastically owing to major changes that took place in supply and demand in tourism industry lead by globalization ( Santos et al, 2022 ). In addition, in a previous research study, it was found that managing change in an organization has become a major issue and challenge for a leader to effectively deploy it ( Herold et al, 2008 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In past research studies, scholars have identified various leadership styles which are practiced in organizations based on the extent of need. However, in today’s fast-growing and competitive world, the sustainability in the tourism industry has knowingly enriched drastically owing to major changes that took place in supply and demand in tourism industry lead by globalization ( Santos et al, 2022 ). In addition, in a previous research study, it was found that managing change in an organization has become a major issue and challenge for a leader to effectively deploy it ( Herold et al, 2008 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The interest of researchers and competitiveness in tourism sustainability has significantly enhanced radically owing to major changes that took place in supply and demand in the tourism industry led by globalization ( Santos et al, 2022 ). Along with competitiveness, the ever-changing world, and shifting focuses of social values, recognition of how past growth has negatively affected the environment has also led to attention toward sustainability more than ever before.…”
Section: Introductionmentioning
confidence: 99%
“…They do not collaborate, caught in this competition of the tourist market. Tourists travel for various reasons, more or less influenced by actors (Santos et al, 2022).…”
Section: Strategies For the Development Of Tourism Products Sold In D...mentioning
confidence: 99%
“…The procedure contributes implicitly to the realisation of social equality and cohesion [57]. According to Santos et al (2022) [58], in order to anchor this much more holistic interpretation of sustainability, a new paradigm needs to be applied in the case of touristic destinations. This theory needs to be manifested on the level of the product as well since the sustainabilityrelated factors in product development are tightly connected to the concept of the circular economy and regenerative systems [59,60].…”
Section: Aspects Of Sustainable Developmentmentioning
confidence: 99%